Ethical values in martial arts stories written by chinese beat generation - Muzaki, Ferril Irham (Resat Bey Mahallesi,Ataturk Caddesi, 2022)
The aim of the study is to present the values ​​of ethical development in the stories of the Chinese bit generation. The development of spiritual values ​​is reflected in culture. The development of character development values ​​is part of the development of character development values. The applied research method is Fairclough's (2001) critical discourse analysis. The stories in question consisted of the stories of 12 Chinese children, namely (1) Astral Pet Store, (2) The apocalypse of the world online, (3) A stormy companion, deliberately pampered by the greatness of the animal (4) Irresistible copying system (5)My vampire system (6) Ultimate Gene Valkyrie, (7) Scholar's advanced technological system, (8) A warrior's promise, (9) I found an apocalyptic world, (10) Sky Digestive Dragon Emperor, (11) Sword Legend, (12) The return of God's war. Data collected from children's references are analyzed. This data analysis consists of three steps. The results of this study are the values ​​of ethical development: (1) the value of cooperation, (2) mutual respect, (3) respect for life, (4) respect for others, and (5) caring for others. The study concludes that (1) these intrinsic values ​​are part of the values ​​of fraternity, (2) the values ​​of character development consist of nationalism and nationalism, and (3) these intrinsic values ​​are part of the learner's autonomy and are taught as a form of learning